(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2015)
Multi-carrier modulation is an attractive technique for fourth generation wireless communication. That information the undesired effects occurring to the distortion techniques can be alleviated with the penalty of the reduced transmission and receiving rates due to introduction of redundancy. MIMO consist of large number of independent subcarriers, MIMO has been widely used in communication systems to meet the demand for increasing data rates. It is robust over multipath fading channels and results in significant reduction of the transceiver complexity. However, one of its disadvantages is sensitivity to carrier frequency offset which causes attenuation, rotation of subcarriers, ISI, CE. MIMO is used for Trans-receive system for increase the channel capacity where the suitable number of antennas is required. Along with OFDM-MIMO with STBCS is considered for wideband transmission to reduced the inter symbol interference ISI and problem of channel estimation CE for fading channels to enhance system capacity, Whereas OFDMMIMO communication has a number of benefits for instance larger bandwidth, reduced power utilization that has made it an gorgeous accomplishment decision for different communication systems including wireless LAN’s. Proposed work investigate the possibility of MIMO technique STBCS based system i.e. MIMO- STBCS for wireless communication. It reduced the problem of MIMO improving bit error rate BER, and system capacity this work implementation on 2x2 & 4x4 MIMO communications